Shooting in SSB IPJ Soccer Players: Coordination, Motivation, and Anxiety - Wardani, M. Fikri; Hidayat, Rachmat; Anuar, Arman Bin; Tunru, Andi Alif (Department of Physical Education, Sport, Health and Recreation, 2023)
The research objective is to determine the correlation between coordination, motivation, and anxiety towards the shooting performance of soccer players in SSB IPJ Kota Palopo. The research method used is a descriptive study with correlational nature. The population in this research consists of soccer athletes from SSB IPJ Kota Palopo. The sampling technique employed is purposive sampling with specific considerations by the researcher, involving a total of 20 soccer athletes as participants in the study. Data analysis was conducted using SPSS version 23.The research results indicate that the coordination variable has a calculated t-score of 4.504, while the critical t-score (t-table) is 2.119. Since the calculated t-score is greater than the critical t-score (t-calculated > t-table), it can be concluded that coordination has a significant influence on shooting performance. Similarly, the motivation variable has a calculated t-score of 4.946, exceeding the critical t-score of 2.119, leading to the conclusion that motivation significantly affects shooting performance. Likewise, the anxiety variable has a calculated t-score of 5.032, which surpasses the critical t-score of 2.119, indicating that anxiety also has a significant impact on shooting performance. From the data analysis, an F-count value of 23.418 and a significance value (sig.) of 0.000 are obtained. Since the F-count value (23.418) is greater than the critical F-value (2.119), and the significance value is less than 0.05 (0.000 < 0.05), H1 is accepted. This implies that collectively, coordination, motivation, and anxiety have a statistically significant impact on shooting performance. With an R-value of 0.902, it can be concluded that the ability of the independent variables to explain the variation in the dependent variable is sufficiently strong.v